2021
DOI: 10.5195/ie.2021.192
|View full text |Cite
|
Sign up to set email alerts
|

Building and Sustaining Community in an Online EdD Program

Abstract: Abstract In this essay, we have described how we build and sustain community in our online EdD program. Initially, we discussed our understanding of community and its influence on our efforts. Then, we discussed three important theoretical frameworks—Wenger’s Community of Practice, Garrison et al.’s Community of Inquiry, and Morris and Stommel’s Critical Digital Pedagogy—and how those frameworks helped to shape our efforts in building and sustaining an online community. Next, we discussed strategies/proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Students of fully online or blended programmes are no less susceptible to a number of the challenges outlined earlier in this paper for those engaging in face-to-face programmes, such as the dangers of isolation, stress, and negative impact on wellbeing in their pursuit of a doctorate, and are likewise in need of support systems in helping them overcome such challenges (Berry, 2019;Deshpande, 2016;Hazell et al, 2020). A difference, however, is that born digital doctoral programmes tend to have mechanisms pre-designed into them for supporting students through community facilitation via digital technologies (Buss & Wolf, 2021). It was clear that we could learn from such programmes as we began to adapt our own for the challenging time that lay ahead.…”
Section: Study Contextmentioning
confidence: 95%
See 2 more Smart Citations
“…Students of fully online or blended programmes are no less susceptible to a number of the challenges outlined earlier in this paper for those engaging in face-to-face programmes, such as the dangers of isolation, stress, and negative impact on wellbeing in their pursuit of a doctorate, and are likewise in need of support systems in helping them overcome such challenges (Berry, 2019;Deshpande, 2016;Hazell et al, 2020). A difference, however, is that born digital doctoral programmes tend to have mechanisms pre-designed into them for supporting students through community facilitation via digital technologies (Buss & Wolf, 2021). It was clear that we could learn from such programmes as we began to adapt our own for the challenging time that lay ahead.…”
Section: Study Contextmentioning
confidence: 95%
“…For instance, programmatic design measures have proven fruitful for creating a sense of community for online doctoral programmes. Buss and Wolf (2021) outline a number of built-in programme components that are designed to foster and sustain community among students of their professional doctorate programme; these include a Leadership Challenge Fishbowl which is designed "to foster development of collaboration and leadership skills and to build community" (p. 49), and a Doctoral Research Conference (DRC) to share and receive feedback on ongoing doctoral research. Similarly, Lively et al (2021) outline how they developed "purposeful programmatic structures focused around building community" (p. 29); they found that the use of immersion experiences, strong support services, synchronous live sessions, and relationships formed with programme staff all contributed to a sense of community for students in their online professional doctorate programme.…”
Section: Sense Of Communitymentioning
confidence: 99%
See 1 more Smart Citation